Developing supplementary Reading material based on the Scramble Method for Junior High Students - Syani Amrulloh, Friendis; Supiani (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This research is aimed to developing supplementary english reading material based on scramble method for first grade of junior high school. Besides, it design supplementary reading materials based on scramble methods. Scramble-type cooperative learning Method is a teaching model by distributing question sheets and answer sheets accompanied by alternative answers that are available randomly. This study uses research and development method which focus on seven steps; need analysis, material development, expert validation, revision I, try-out, revision II, and final product. The result shows that the scramble materials were helpful for the students in comprehending the text because they were already familiar with Indonesian culture. The students learned more about Indonesian culture, making them more aware of their local culture and helping them learn reading